The Influence of Fillet Step on Backward-Facing Step Flow Characteristics - Julian, James; Anggara, Rizki Aldi; Wahyuni, Fitri (P3M Politeknik Negeri Cilacap, 2023)
Backward-facing step (BFS) is a model that provides several applicative features in engineering. The complex phenomena of BFS flow have a crucial impact on any application. Therefore, this study comprehensively investigates the flow characteristics of BFS with various step shapes. The backward-facing step (F-BFS) fillets were tested at intervals of Reynolds number 50 smaller than Re smaller than 400 using the CFD approach. Based on the computational results, it was found that flow separation is a fundamental phenomenon in BFS flow. Due to sudden expansion, Flow separation forms a recirculation area which continues to increase almost linearly with an increase in the Reynolds number. The recirculation area contains unstable rotating vortexes, which can impact the flow efficiency of BFS. Using a different step shape proves that F-BFS can minimize the recirculation area to increase the efficiency of the BFS flow.